Analysis of The Differences in the Financial Performance of The GKJ Pension Fund before and During the Covid-19 Pandemic - Endang Purwanti (ProBisnis : Jurnal Manajemen, 2023)
This research aims to determine the Differences in the Financial Performance of the GKJ Pension Fund before and during the COVID-19 pandemic using Return On Investment (ROI), Operational Cost Efficiency (OCE), Investment Cost Efficiency (ICE), and Fund Sufficiency Ratio (FSR). The research results indicate that there is no significant difference in Return On Investment (ROI) before and during the COVID-19 pandemic, suggesting that the ability to generate ROI remains consistent before and during the pandemic. There is no significant difference in Operational Cost Efficiency (OCE) before and during the COVID-19 pandemic, indicating that the GKJ pension fund can achieve operational cost efficiency both before and during the pandemic. Investment Cost Efficiency (ICE) shows no significant difference before and during the COVID-19 pandemic, likely because thorough analysis is conducted before making investments, considering both investment returns and costs. The Fund Sufficiency Ratio (FSR) shows a significant difference before and during the COVID-19 pandemic, attributed to the growth of net assets used as a funding source being smaller than actuarial obligations. The COVID-19 pandemic led to an increase in actuarial obligations. The GKJ Pension Fund needs to enhance the Fund Sufficiency Ratio in order to demonstrate the quality of the GKJ Pension Fund.